Peningkatan Kemampuan Berpikir Tingkat Tinggi Siswa SMAN 1 Tanjung Jabung Timur pada Materi Sel Melalui Model Pembelajaran Discovery Learning: Improving the Higher Thinking Ability of SMAN 1 Tanjung Jabung Timur Students on Cell Materials Through the Discovery Learning - Melli Ismawati; Muhaimin Muhaimin; Yusnaidar Yusnaidar (Universitas Jambi, 2021)
This study aims to improve higher-level thinking skills using the discovery learning model in class XI IPA 3 SMAN 1 Tanjung Jabung Timur on cell material. The research is a classroom action research consisting of planning, implementation, observation, and reflection. The instruments used were observation sheets of student and teacher activities and learning achievement tests. The data analysis technique used is descriptive quantitative and qualitative analysis. The study results show that the stages of discovery learning syntax make it easier for students to understand concepts and analyze and evaluate the problems encountered when learning occurs. In addition, implementing learning using the discovery learning model is carried out in a good category. The increase in the affective domain reached a score of 3.15 (good category); in the psychomotor domain, it achieved a score of 2.76 (good category); while in the cognitive domain, it can improve higher-order thinking skills with average learning outcomes reaching the completeness criteria and achieving a score of 76.7. Based on these results, learning with the discovery learning model can provide opportunities and help students to understand a material concept and develop their creativity independently.